Public Economics and Startup Entrepreneurs - Robin Boadway; Jean-François Tremblay (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper surveys the various forms of market failure that can arise when innovating entrepreneurs consider entering an industry, and outlines possible implications for public policy. Externalities can arise from entrepreneurial activities such as spillover benefits from new innovations and spillover costs on incumbent firms. New entrepreneurs can also face various barriers to entry, either natural ones or those created by incumbent firms or government policy. They may also face problems in obtaining credit at efficient terms if there are information asymmetries in markets for either loan or equity finance. Finally, asymmetric information may also plague new firms in the hiring of workers. These various inefficiencies are of contradictory sign, some calling for an incentive to startup firms and other for the opposite. Thus, public policy is ambiguous and depends on the circumstances at hand.
Keywords: 330